Housing Issues in Tyumen during Late 1970s to Early 1980s: Social Conditions, Expectations, and Reality - I. V. Skipina; A. A. Chernyshev (Научный диалог)
This study investigates the social conditions and expectations of the population in Tyumen during the late 1970s to early 1980s. It explores potential solutions to the housing shortage faced by the city. The novelty of this research lies in its use of legislative materials, administrative records, statistics, personal recollections, periodicals, and documents sourced from the State Archive of Tyumen Region, which reveal trends in the improvement of living conditions for a significant number of Tyumen residents during this period. The article analyzes the socially-oriented nature of the “mass housing construction” policy, highlighting both the successes and challenges encountered in its implementation. Evaluations of housing quality provided by commissions and new residents are presented. The study also examines the factors that hindered the achievement of set objectives. The authors conclude that panel construction alleviated the severity of the “housing question,” yet failed to resolve it entirely, as the number of apartments built did not meet the growing demands of the population. By the early 1980s, the pace of construction had slowed, indicating “stagnation” within the economy and the need for program adjustments, which ultimately did not occur. It is emphasized that the “housing question” remains a socially significant issue, and attempts to address it during the Soviet era warrant further investigation to draw lessons from the past.